2020
DOI: 10.1113/ep089073
|View full text |Cite
|
Sign up to set email alerts
|

Myths and methodologies: Reliability of forearm cutaneous vasodilatation measured using laser‐Doppler flowmetry during whole‐body passive heating

Abstract: Laser‐Doppler flowmetry (LDF) is commonly used to assess cutaneous vasodilatation responses, but its reliability (i.e. consistency) during whole‐body passive heating is unknown. We therefore assessed the reliability of LDF‐derived indices of cutaneous vasodilatation during incremental whole‐body heating. Fourteen young men (age: 24 (SD 5) years) completed three identical trials, each separated by 1 week. During each trial, a water‐perfused suit was used to raise and clamp oesophageal temperature at 0.6°C (low‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Second, without the use of a normalization procedure, it remains difficult to compare between various sites and individuals using the absolute SkBF and CVC values in human studies. Indeed, a prior study has shown that the absolute resting CVC values within participants were poor between days but improved with the application of heat strain ( Gemae et al, 2021 ). Thus, caution is advised when interpreting SkBF data where comparisons between individuals or locations are made.…”
Section: Discussionmentioning
confidence: 99%
“…Second, without the use of a normalization procedure, it remains difficult to compare between various sites and individuals using the absolute SkBF and CVC values in human studies. Indeed, a prior study has shown that the absolute resting CVC values within participants were poor between days but improved with the application of heat strain ( Gemae et al, 2021 ). Thus, caution is advised when interpreting SkBF data where comparisons between individuals or locations are made.…”
Section: Discussionmentioning
confidence: 99%
“…Further, all participants were habitually active (i.e., performed ≥30 min of structured physical activity at least twice per week) as determined by a standardized questionnaire (Baecke et al, 1982). Data from the young men have been reported as part of a larger project assessing the reliability of microvascular, sudomotor, and cardiovascular autonomic function (Akerman et al, 2021; Gemae et al, 2021; Rutherford et al, 2021). Given the exploratory nature of the study, no a priori power analysis was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed one screening session and one experimental session in a temperature‐controlled laboratory (~25°C). The experimental sesssion for the young group was the first of three sessions reported in our previous work (Akerman et al, 2021; Gemae et al, 2021; Rutherford et al, 2021). The firstexperimental session for the young group was chosen as it provided the most naïve assessment between both age groups.…”
Section: Methodsmentioning
confidence: 99%
“…half-width) of a 95% confidence interval for the paired difference between means (Maxwell et al, 2008). The upper 10% threshold (in units of cutaneous vascular conductance normalized to maximum vasodilatation; % CVC max ) was defined a priori as the smallest effect size of interest (SESOI; Anvari & Lakens, 2021;Gemae et al, 2021; see below for further explanation). A sample size based on a maximum precision of 5% CVC max (i.e.…”
Section: Sample Size Estimationmentioning
confidence: 99%
“…To evaluate the potential importance of between-region differences in the NO contribution to local skin heating, we identified the SESOI (i.e. the smallest between-region difference that we would not want to miss) a priori (Anvari & Lakens, 2021;Gemae et al, 2021). By examining previous research, we determined that acute ischaemic stress, ageing and chronic disease were consistently associated with alterations in the plateau response to local heating by as little as 10% CVC max (Black et al, 2008;Minson et al, 2002;Stewart et al, 2008).…”
Section: Smallest Effect Size Of Interestmentioning
confidence: 99%